Facial hyperalgesia due to direct action of endothelin-1 in the trigeminal ganglion of mice. (23rd March 2018) - Gomes, Lenyta Oliveira; Chichorro, Juliana Geremias; Araya, Erika Ivanna; de Oliveira, Jade; Rae, Giles Alexander
Abstract: Objective: This study assessed the ability of endothelin-1 (ET-1) to evoke heat hyperalgesia when injected directly into the trigeminal ganglia (TG) of mice and determined the receptors implicated in this effect. The effects of TG ETA and ETB receptor blockade on alleviation of heat hyperalgesia in a model of trigeminal neuropathic pain induced by infraorbital nerve constriction (CION) were also examined. Methods: Naive mice received an intraganglionar (i.g.) injection of ET-1 (0.3–3 pmol) or the selective ETB R agonist sarafotoxin S6c (3–30 pmol), and response latencies to ipsilateral heat stimulation were assessed before the treatment and at 1-h intervals up to 5 h after the treatment. Heat hyperalgesia induced by i.g. ET-1 or CION was assessed after i.g. injections of ETA R and ETB R antagonists (BQ-123 and BQ-788, respectively, each at 0.5 nmol). Key findings: Intraganglionar ET-1 or sarafotoxin S6c injection induced heat hyperalgesia lasting 4 and 2 h, respectively. Heat hyperalgesia induced by ET-1 was attenuated by i.g. BQ-123 or BQ-788. On day 5 after CION, i.g. BQ-788 injection produced a more robust antihyperalgesic effect compared with BQ-123. Conclusions: ET-1 injection into the TG promotes ETA R/ETB R-mediated facial heat hyperalgesia, and both receptors are clearly implicated in CION-induced hyperalgesia in the murine TG system.